Foreign Direct Investments - Theoretical Aspect - Stawicka, Magdalena Kinga (Bezpośrednie inwestycje zagraniczne - aspekt teoretyczny, 2009)
Theories of foreign direct investments try to explain the reasons of establishing international enterprises, understand their motives for making investments outside their native states as well as study factors afifecting the selection of localization for their business activity. The goal of this article is the presentation of categorized theories, which are published in Polish subject-matter literature and in foreign literature, concerning direct foreign investments.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 143-151
Keywords: FDI; theory; foreign direct investment